Identification of Hearing Loss Based on Hearing Tresholds Using Pure-Tone Audiometry - Jayanti, Atmi Dwi (Jurusan Teknik Elektromedik, Politeknik Kesehatan Kemenkes Surabaya, Indonesia, 2024)
ABSTRACT Hearing loss is a condition in which there is a disorder in the normal hearing process in one or both ears. Hearing loss conditions based on the hearing threshold are mild, moderate, severe, and very severe hearing loss. To find out hearing loss, an audiometry examination can be performed. Audiometry is a tool that functions to determine the function of hearing and the degree of deafness experienced by the patient. The purpose of this study is to apply hearing threshold for the identification of hearing loss using pure-tone audiometry. The results when tested on the module compared with conventional audiometry equipment showed that there was an average value difference between manual mode and audiometry in the left ear, which was between 1.00dB to 5.00dB (1.00% to 20.0%) and in the right ear between 1.25dB to 3.75dB (4.2% to 30.0%). Although there is a difference in the calculation of the average value of the hearing threshold, the average value of the hearing threshold still shows in the same range of hearing threshold degrees of deafness between manual mode, automatic mode and in the audiometry device used as a comparison.